Methodology for Detecting Similarity of Program Code Based on Combining Algorithms - Novotochinov, Maksim E.; Solomatin, Dmitry I.; Chernenkii, Andrei V. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2024)
In this paper, the main existing strategies used in plagiarism of program code were investigated, as well as the most popular approaches used to identify copied texts were analyzed. Based on the results of the analysis of various approaches, as well as the analysis of the subject area itself, the requirements for the new system were formulated. Further, this system was successfully designed, implemented and tested. The most suitable areas for the application of the developed system are education (universities, colleges and other educational institutions can use the system to check the code written by students in order to detect plagiarism) and programming competitions.